The Devil in the Details: Beelzebul and Social Identity Complexity in Mark 3:20–35 - Jeremy D. Otten (Religions, 2023)
While the origin and etymology of the name Beelzebul have received some scholarly attention, very little attention has been given to the more basic question of why the scribes would choose this particular name for their accusations, or why Jesus would shift discussion to speak of Satan. This study examines Mark 3:20–35 through the lens of Social Identity Theory (SIT) and Social Identity Complexity Theory (SIC) to reveal the underlying values and motivations behind the use of the two different names in the challenge and riposte between Jesus and the scribes. The scribes speak of “Beelzebul” as part of their attempt to discredit and even prosecute Jesus according to Deut 13, whereas Jesus’s reference to “Satan” reframes the discussion in light of the cosmic battle between those who do God’s will and the one who opposes it. In so reframing the discussion, he redraws the lines of ingroup and outgroup identity for his hearers and for Mark’s audience.